Optimization and Characterization of Xylanase from An Indigenous Strain of Aureobasidium Pullulans - Rahi, Deepak K.; Richa; Kaur, Maninderjeet (International Journal of Scientific Research in Biological Sciences, 2018)
Xylanases are versatile hydrolytic enzymes in nature, due to its degradatory properties and ability to degrade hemicelluloses efficiently. Xylanases and associated debranching enzymes produced by a variety of microorganisms including bacteria, actinomycetes, yeast and fungi bring hydrolysis of hemicelluloses. Among microorganisms, filamentous fungi are the predominant source organism for xylanases. Xylanases have fortified awesome interest because of their potential application in a many industries. Throughout the years, the quantity of conceivable uses of xylanases in the paper and pulp industry has expanded relentlessly, and a few applications have been popularized. In present investigation an indigenous species of Aureobasidium pullulans was evaluated for xylanse producing efficiency and various parameters affecting the production was standardized employing one-factor at a time approach. This resulted in significant enhancement of enzyme activity from 8.7 U/ml to 27.75 U/ml. The enzyme optima for pH and temperature were found to be 6 and 55 °C respectively.